Steel for transporting and storing liquid ammonia

By using austenitic stainless steel with specific components to make containers, the problem of not being used for both liquid ammonia and liquid natural gas at the same time is solved, and flexible use of containers and reduced transportation costs are achieved.

CN119816615APending Publication Date: 2025-04-11GAS & HEAT SPA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380063866.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-05
Filing Date
2023-09-05
Publication Date
2025-04-11

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0005297799680000011
    Figure HDA0005297799680000011
Patent Text Reader

Abstract

The invention relates to the use of special steel in the manufacture of a container for the storage and transport of liquid ammonia, such as a depot or a storage tank.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the use of special steel in manufacturing containers for storing and transporting liquid ammonia, such as storage tanks or reservoirs. Background Art

[0002] The transportation and storage of liquid fuels such as liquefied natural gas (LNG) or liquid ammonia require special precautions and the use of specific materials for the construction of containers, reservoirs or tanks dedicated to these operations.

[0003] In fact, the containers should be able to withstand the specific conditions of use for each type of fuel, usually very low temperatures and pressures of several bars to keep the fuel in liquid state (usually, T = -163 ° C, P = 3-3.5 bar for LNG and T = -33 ° C, P = 3-3.5 bar for liquid ammonia), while showing sufficient resistance to stress corrosion. This is both for safety reasons and to guarantee their adequate continued use over a long period of time.

[0004] The container must therefore have high performance both in terms of mechanical strength at low temperatures and corrosion resistance under stress characteristics, wherein the latter should also be sufficient depending on the specific type of liquid fuel being transported.

[0005] Until now, industry guidelines (IGC - International Gas Code) have specified specific materials for the groups of fuels that need to be transported, with for example a common specific transport temperature range. These guidelines also set additional requirements for some fuels that are more difficult to handle.

[0006] Thus, the materials currently known in the art are materials that are specialized for specific liquid fuels, such as for liquid ammonia or liquid natural gas (LNG).

[0007] This fact, on the one hand, still ensures suitable and specific properties of the liquid fuel and safe transportation and storage conditions, but on the other hand, limits the flexibility of operators in the industry in storage and transportation operations, thus preventing the possibility of using the same container to transport two different fuels such as LNG and liquid ammonia at the same time in separate compartments or at different times after appropriate cleaning operations.

[0008] As a result, there is a complete lack of containers on the market that can be used to store and transport different fuels.

[0009] Brief description of the invention

[0010] The aim of the present invention is to overcome these limitations of storage and transport operational flexibility by providing the possibility to use the same container for transporting and storing two different liquid fuels, such as LNG and liquid ammonia.

[0011] In particular, the applicant unexpectedly discovered that a steel known in the industry as being suitable for manufacturing containers for storing and transporting LNG can be used for manufacturing containers for storing and transporting liquid ammonia, the steel comprising 15.5-17.5 wt. % chromium (Cr), 6.0-8.0 wt. % manganese (Mn), 3.5-5.5 wt. % nickel (Ni), 0.10-0.25 wt. % nitrogen (N), 0.001-0.05 wt. % carbon (C) and 66.0-75.0 wt. % iron (Fe).

[0012] Therefore, in a first aspect of the present invention, the present invention relates to the use of austenitic stainless steel in the manufacture of containers for storing and transporting liquid ammonia, wherein the austenitic stainless steel comprises 15.5 to 17.5 wt. % chromium (Cr), 6.0 to 8.0 wt. % manganese (Mn), 3.5 to 5.5 wt. % nickel (Ni), 0.10 to 0.25 wt. % nitrogen (N), 0.001 to 0.05 wt. % carbon (C) and 66.0 to 75.0 wt. % iron (Fe).

[0013] The austenitic stainless steel may also include other elements such as silicon (Si), phosphorus (P), sulfur (S), copper (Cu), titanium (Ti), molybdenum (Mo) and niobium (Nb). In this embodiment, the steel contains silicon (Si), copper (Cu), titanium (Ti) and molybdenum (Mo), each of which has a weight percentage concentration less than or equal to 1.2 weight %.

[0014] Preferably, the austenitic stainless steel contains silicon (Si), copper (Cu), titanium (Ti) and molybdenum (Mo), each having a weight percentage concentration lower than or equal to 1.2%, and preferably includes phosphorus (P) and sulfur (S), each having a weight percentage concentration lower than or equal to 0.06%.

[0015] Preferably, the austenitic stainless steel contains 16.0 to 17.0 wt % chromium (Cr), 6.4 to 7.5 wt % manganese (Mn), 4.0 to 5.0 wt % nickel (Ni), 0.15 to 0.20 wt % nitrogen (N), and 0.001 to 0.03 wt % carbon (C).

[0016] More preferably, the austenitic steel contains about 16.5 wt % chromium (Cr), about 7 wt % manganese (Mn), about 4.7 wt % nickel (Ni), about 0.15 wt % nitrogen (N), and 0.025 wt % carbon (C).

[0017] In fact, the Applicant has surprisingly discovered that said steel exhibits mechanical properties and corrosion resistance to liquid ammonia making it suitable for the storage and transport of liquid fuels other than LNG.

[0018] In this manner, Applicants have surprisingly appreciated that the same container may be used for transporting and storing two different fuels, such as LNG and liquid ammonia.

[0019] For operators in this sector, this brings clear advantages in terms of flexibility in the use of containers and rationalization of transport, allowing, for example, the transport of liquid natural gas (LNG) first in the same container or in a first compartment and subsequently liquid ammonia in a second compartment, thus gaining a competitive advantage over the existing technology of transport and storage operations, which requires the use of two different containers (and two carriers).

[0020] Therefore, in some further aspects of the present invention, the present invention also relates to a container for storing or transporting liquid ammonia and the use of the container in storing or transporting liquid ammonia, the container comprising a main body made of austenitic stainless steel as defined in the first aspect of the present invention, and wherein the main body comprises at least one joint made of a filler material, the filler material comprising 15 to 25 weight % of chromium (Cr), 2 to 4 weight % of molybdenum (Mo), 14 to 18 weight % of nickel (Ni), 6-8 weight % of manganese (Mn), 0.13-0.20 weight % of nitrogen (N) and 0.01-0.04 weight % of carbon (C).

[0021] The container may naturally have any shape, such as spherical, cylindrical or bilobed, or other shapes known in the art or in any case designed to contain ammonia.

[0022] The advantages of the container and the use according to these further aspects of the invention have already been highlighted with reference to the first aspect of the invention and will not be elaborated here.

[0023] Due to the properties of the container according to the invention, it is possible to use the container to store or transport liquid ammonia as well as liquid natural gas.

[0024] Therefore, in a further aspect thereof, the present invention also relates to a method for storing or transporting liquid ammonia, the method comprising storing or transporting liquid ammonia in the container; and to a method for storing or transporting two fuels, wherein at least one fuel is liquid ammonia and the other is preferably LNG, the method comprising the step of simultaneously storing or transporting the two fuels in two separate compartments of the same container, wherein the container is made of austenitic stainless steel as defined in the first aspect of the present invention.

[0025] The advantages of the method according to these further aspects of the invention have already been highlighted with reference to the first aspect of the invention and will not be elaborated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In the attached figure:

[0027] - Figure 1The images of 12 samples used for stress corrosion testing according to Example 1 are shown, specifically, three samples are not welded (samples #1 to #3), and nine samples are welded (samples #4 to #12);

[0028] - Figure 1A Shown are images of two samples mounted in an apparatus for conducting stress corrosion testing of Example 1, one without welding (A) and one with welding (B);

[0029] - Figure 2-13 Surface micrographs of samples #1 to #12 after stress corrosion testing according to Example 1 are shown. Specifically, Figure 2 A micrograph of sample #1 is shown; Figure 3 A micrograph of sample #4 is shown; Figure 4 A micrograph of sample #5 is shown; Figure 5 A micrograph of sample #6 is shown; Figure 6 A micrograph of sample #2 is shown; Figure 7 A micrograph of sample #7 is shown; Figure 8 A micrograph of sample #8 is shown; Fig. 9 A micrograph of sample #9 is shown, Fig.10 A micrograph of sample #3 is shown; Fig.11 A micrograph of sample #10 is shown, Fig.12 A micrograph of sample #11 is shown, Fig.13 A micrograph of sample #12 is shown; and

[0030] - Figure 14-19 The tomographic images of the cross-section (1 / 3 (A), 2 / 3 (B) and 3 / 3 (C) of the full thickness) and the longitudinal direction (1 / 3 (A) and 2 / 3 (B) of the full thickness) of the surfaces of samples #6, #8 and #12 after the stress corrosion test according to Example 1 are shown. Specifically, Fig.14 Tomograms of a cross section of sample #6 are shown at (A) 1 / 3, (B) 2 / 3, and (C) 3 / 3 through the section; Fig.15 Tomographic scans of the longitudinal section of sample #6 at (A) 1 / 3 and (B) 2 / 3 through the section are shown; Fig.16 Tomographic scans of a cross section of sample #8 at (A) 1 / 3, (B) 2 / 3, and (C) 3 / 3 through the section are shown; Fig.17 Tomographic scans of the longitudinal section of sample #8 at (A) 1 / 3 and (B) 2 / 3 through the section are shown; Fig.18 Tomograms of a cross section of sample #12 at (A) 1 / 3, (B) 2 / 3, and (C) 3 / 3 through the section are shown; Fig.19Tomograms of the longitudinal cross section of sample #12 at (A) 1 / 3 and (B) 2 / 3 through the cross section are shown. DETAILED DESCRIPTION OF THE INVENTION

[0032] In a first aspect of the invention, the invention relates to the use of austenitic stainless steel in the manufacture of containers for storing and transporting liquid ammonia, wherein the austenitic stainless steel comprises 15.5 to 17.5 wt. % chromium (Cr), 6.0 to 8.0 wt. % manganese (Mn), 3.5 to 5.5 wt. % nickel (Ni), 0.10 to 0.25 wt. % nitrogen (N), 0.001 to 0.05 wt. % carbon (C) and 66.0 to 75.0 wt. % iron (Fe).

[0033] In fact, the Applicant has surprisingly discovered that said steel exhibits mechanical properties and corrosion resistance properties making it suitable also for the storage and transport of liquid ammonia.

[0034] Further advantageous aspects of the method according to the invention are described more extensively and in detail in the above brief description of the invention and are an integral part of the present description, but are not repeated here.

[0035] In the present specification and the following claims, unless otherwise indicated, all numerical values ​​indicating quantities, parameters, percentages, etc. are preceded by the term "about" in all cases. In addition, except for the ranges specifically indicated below, all numerical ranges include all possible combinations of maximum and minimum values ​​and all possible intermediate ranges.

[0036] The present invention may have one or more of the preferred features disclosed below in one or more of its aspects, and these features may be combined with each other as required by the application.

[0037] Preferably, the austenitic stainless steel according to the present invention contains 16.0 to 17.0 wt. % chromium (Cr), 6.4 to 7.5 wt. % manganese (Mn), 4.0 to 5.0 wt. % nickel (Ni), 0.15 to 0.20 wt. % nitrogen (N) and 0.001 to 0.03 wt. % carbon (C), more preferably about 16.5 wt. % chromium (Cr), about 7 wt. % manganese (Mn), about 4.7 wt. % nickel (Ni), about 0.15 wt. % nitrogen (N) and about 0.025 wt. % carbon (C).

[0038] The austenitic stainless steel may further contain additional elements such as silicon (Si), phosphorus (P), sulfur (S), copper (Cu), titanium (Ti), molybdenum (Mo), or niobium (Nb).

[0039] Preferably, the steel contains silicon (Si), copper (Cu), titanium (Ti) and molybdenum (Mo), each having a weight percent concentration lower than or equal to 1.2 weight percent, and preferably contains phosphorus (P) and sulfur (S), each having a weight percent concentration lower than or equal to 0.06 weight percent.

[0040] More preferably, the steel contains at most 0.75 wt. % silicon (Si) and at most 1.0 wt. % copper (Cu).

[0041] Advantageously, the steel contains at most 0.045 wt. % phosphorus (P), at most 0.015 wt. % sulphur (S), at most 0.1 wt. % titanium (Ti) and at most 0.75 wt. % molybdenum (Mo).

[0042] Obviously, the steel according to the invention also contains iron (Fe) as a main component, which is preferably present in an amount of about 66 wt. % to about 75 wt. %.

[0043] In a particularly preferred embodiment, the steel according to the invention is of AISI 201LN (USN S20153) type.

[0044] Therefore, the present invention also relates to a container for storing or transporting liquid ammonia and the use of the container in storing or transporting liquid ammonia, the container comprising a main body made of austenitic stainless steel as defined in the first aspect of the present invention, and wherein the main body comprises at least one joint made of a filler material, the filler material comprising 15 to 25 weight % of chromium (Cr), 2 to 4 weight % of molybdenum (Mo), 14 to 18 weight % of nickel (Ni), 6-8 weight % of manganese (Mn), 0.13-0.20 weight % of nitrogen (N) and 0.01-0.04 weight % of carbon (C).

[0045] The advantages of the container and the use according to these further aspects of the invention have already been highlighted with reference to the first aspect of the invention and will not be elaborated here.

[0046] For the purposes of the present invention, the term "container" refers to any item known to those skilled in the art and suitable for containing a liquid fuel, in this case liquid ammonia.

[0047] The container according to the invention may be of virtually any type known to the person skilled in the art for storing and transporting liquid ammonia, for example a tank, a container or a reservoir.

[0048] Furthermore, the container according to the invention may have any shape, such as spherical, cylindrical or bilobed, or other shapes known in the industry or in any case designed to contain liquid ammonia.

[0049] Furthermore, the container according to the invention can advantageously be used, placed or transported on any carrier or mode of transport, such as by sea, road, rail or air.

[0050] For example, in one embodiment, a container according to the present invention may be a storage tank placed on a tanker truck.

[0051] In an alternative embodiment of the invention, the container may be a storage tank located on a port terminal.

[0052] The container according to the invention can also be manufactured according to any production technology known to a person skilled in the art and suitable for the intended purpose; in particular, it is known to weld together the steel plates constituting the container in the presence of specific gas mixtures, using specific filling materials, the combinations of which are known to a person skilled in the art and are commonly indicated by those who produce and sell the same materials and mixtures.

[0053] In the case of a container according to the invention, the latter comprises at least one joint, more preferably all joints, made of a filler material comprising 15 to 25 wt.-% chromium (Cr), 2 to 4 wt.-% molybdenum (Mo), 14 to 18 wt.-% nickel (Ni), 6 to 8 wt.-% manganese (Mn), 0.13 to 0.20 wt.-% nitrogen (N) and 0.01 to 0.04 wt.-% carbon (C).

[0054] Preferably, the filler material contains 20 to 20.5 wt % chromium (Cr), about 3 wt % molybdenum (Mo), 15.5 to 16 wt % nickel (Ni), 7 to 7.5 wt % manganese (Mn), 0.15 to 0.18 wt % nitrogen (N), and 0.015 to 0.03 wt % carbon (C).

[0055] The filler material may also advantageously include other elements, such as phosphorus (P), sulfur (S), silicon (Si), molybdenum (Mo), copper (Cu), titanium (Ti), niobium (Nb).

[0056] Obviously, the filler material also includes iron (Fe) as a main component, which is preferably present in an amount of about 55 wt % to about 63 wt %.

[0057] In a preferred embodiment, the filler material is AISI 316LMn steel.

[0058] Due to the properties of the container according to the invention, liquid ammonia as well as liquid natural gas can be stored or transported using the container.

[0059] Therefore, in a further aspect of the present invention, the present invention relates to a method for storing or transporting liquid ammonia, the method comprising storing or transporting liquid ammonia in the container; and to a method for storing or transporting two fuels, wherein at least one fuel is liquid ammonia and the other is preferably LNG, the method comprising the step of storing or transporting the two fuels simultaneously in two separate compartments of the same container, wherein the container is made of austenitic stainless steel as defined in the first aspect of the present invention.

[0060] The advantages of the method according to these further aspects of the invention have already been highlighted with reference to the first aspect of the invention and will not be elaborated here.

[0061] The invention will now be illustrated by means of some examples which are intended to be illustrative rather than limiting. DETAILED DESCRIPTION

[0062] method

[0063] • EN ISO 7539-2:1995: Corrosion of metals and alloys - Stress corrosion testing (Part 2: Preparation and use of bent beam specimens);

[0064] • EN ISO 7539-1:2012: Corrosion of metals and alloys – Stress corrosion testing (Part 1: General guidance on the test procedure);

[0065] • EN ISO 7539-8:2008: Corrosion of metals and alloys – Stress corrosion testing (Part 8: Preparation and use of specimens for evaluation of welds);

[0066] • ISO 16540:2015: Corrosion of metals and alloys – Method for determination of stress corrosion cracking resistance of metals by four-point bending method;

[0067] • ASTM B858-06:2018: Standard Test Method for Determining Susceptibility of Copper Alloys to Stress Corrosion Cracking by Ammonia Vapor Testing;

[0068] • UNI EN ISO 6892-1:2020 B: Metallic materials - Tension tests (Part 1: Test methods at room temperature);

[0069] • UNI EN ISO 3452-1:2021: Non-destructive testing - Penetrant testing (Part 1: General principles);

[0070] Example 1 - Verification of AISI 201LN Steel Compatibility for Ammonia Using Stress Corrosion Testing

[0071] Twelve samples having the characteristics shown in Table 1 below were prepared for testing.

[0072] Table 1

[0073]

[0074] Three samples (#1, #2 and #3) consisted of metal body parts only, while the remaining nine samples (#4-#12) contained a joint with a cross weld with filler metal in the center of the sample. The welding was performed using the 135 / GMAW (gas metal arc welding) process according to WPS GH101-WPS-6a-0.

[0075] Throughout the test, the samples were loaded and subjected to four-point bending (FPB) to a minimum yield strength of 310 MPa; Young's modulus was 200 GPa.

[0076] The load remains constant throughout the test. As an example, Figure 1A Two specimens (with and without a weld joint, B and A, respectively) that were loaded and bent in this manner are shown.

[0077] The tests were carried out under three different conditions that represent as closely as possible the environmental conditions encountered during the storage and transport of ammonia.

[0078] Test #1 - Ambient pure ammonia (≥99.5%) in the vapor phase at 25°C and atmospheric pressure for 720 hours: Samples #1, #4, #5, and #6;

[0079] Test #2 - Ambient pure ammonia (≥99.5%) in the vapor phase at -20°C and atmospheric pressure for 720 hours: Samples #2, #7, #8, and #9;

[0080] Test #3 - Ambient pure ammonia (≥99.5%) in liquid phase at -33°C and atmospheric pressure for 720 hours: Samples #3, #10, #11 and #12.

[0081] Therefore, in each condition, one base material and three welded samples were kept in the test chamber.

[0082] At the end of the test, the 12 samples were visually inspected using a stereo microscope at a magnification of at least 10 times to detect any visible surface cracks. As a result of the microscopic analysis, none of the samples showed the formation of visible surface cracks. Figure 2-Figure 13 Surface micrographs of samples #1 to #12 are shown; a reference scale is shown at the bottom right of each micrograph.

[0083] The samples are then inspected using a fluorescent penetrant liquid according to UNI EN ISO 3452-1:2021 Level 4 to ensure that there are no cracks on the sample surface attributable to stress corrosion cracking testing.

[0084] As a result of the analyses performed, none of the samples showed crack formation as a result of the tests performed.

[0085] Finally, to complete the analysis, a tomographic scan was performed on the welded specimens for each test condition to highlight any cracks present inside the specimen. Longitudinal and cross-sectional scans were performed at different depths through the thickness.

[0086] In Table 2 below, the scanning parameters are summarized.

[0087] Table 2

[0088]

[0089] Fig.14 and Fig.15 Shown are cross-sectional (1 / 3 (A), 2 / 3 (B), and 3 / 3 (C) full thickness) and longitudinal (1 / 3 (A) and 2 / 3 (B) full thickness) tomographic images of the surface of sample #6 after testing under test #1 conditions.

[0090] Fig.16 and Fig.17 Shown are cross-sectional (1 / 3 (A), 2 / 3 (B), and 3 / 3 (C) full thickness) and longitudinal (1 / 3 (A) and 2 / 3 (B) full thickness) tomographic images of the surface of sample #8 after testing under test #2 conditions.

[0091] Fig.18 and Fig.19 Shown are cross-sectional (1 / 3 (A), 2 / 3 (B), and 3 / 3 (C) full thickness) and longitudinal (1 / 3 (A) and 2 / 3 (B) full thickness) tomographic images of the surface of sample #12 after testing under test #3 conditions.

[0092] As a result of the analyses performed, none of the samples showed crack formation inside the sample.

[0093] Therefore, all tests showed perfect compatibility of AISI 201LN steel with liquid ammonia.

Claims

1. Use of austenitic stainless steel in the manufacture of a container for storing and transporting liquid ammonia, the austenitic stainless steel comprising 15.5 to 17.5 wt % chromium (Cr), 6.0 to 8.0 wt % manganese (Mn), 3.5 to 5.5 wt % nickel (Ni), 0.10 to 0.25 wt % nitrogen (N), 0.001 to 0.05 wt % carbon (C) and 66.0 to 75.0 wt % iron (Fe).

2. The method according to claim 1, wherein the steel comprises 16.0 to 17.0 wt. % chromium (Cr), 6.4 to 7.5 wt. % manganese (Mn), 4.0 to 5.0 wt. % nickel (Ni), 0.15 to 0.20 wt. % nitrogen (N) and 0.001 to 0.03 wt. % carbon (C).

3. Use according to claim 1 or 2, wherein the steel comprises about 16.5 wt. % chromium (Cr), about 7 wt. % manganese (Mn), about 4.7 wt. % nickel (Ni), about 0.15 wt. % nitrogen (N) and about 0.025 wt. % carbon (C).

4. Use according to any one of claims 1 to 3, wherein the steel contains silicon (Si), phosphorus (P), sulfur (S), copper (Cu), titanium (Ti), molybdenum (Mo) and niobium (Nb).

5. Use according to claim 4, wherein the steel contains silicon (Si), copper (Cu), titanium (Ti) and molybdenum (Mo), each having a weight percent concentration lower than or equal to 1.2 weight percent.

6. Use according to claim 5, wherein the steel comprises at most 0.75 wt. % silicon (Si) and at most 1.0 wt. % copper (Cu).

7. Use according to claim 4, wherein the steel contains phosphorus (P) and sulfur (S), each having a weight percent concentration lower than or equal to 0.06 weight percent.

8. Use according to any one of claims 1 to 7, wherein the steel is of AISI 201LN (USN S20153) type steel.

9. A container for storing or transporting liquid ammonia, the container comprising a body made of austenitic stainless steel as defined in any one of claims 1 to 8, and wherein the body comprises at least one joint made of a filler material comprising 15 to 25 wt % of chromium (Cr), 2 to 4 wt % of molybdenum (Mo), 14 to 18 wt % of nickel (Ni), 6-8 wt % of manganese (Mn), 0.13-0.20 wt % of nitrogen (N) and 0.01-0.04 wt % of carbon (C).

10. The container of claim 9, wherein the filler material comprises 20 to 20.5 wt% chromium (Cr), about 3 wt% molybdenum (Mo), 15.5 to 16 wt% nickel (Ni), 7 to 7.5 wt% manganese (Mn), 0.15 to 0.18 wt% nitrogen (N), and 0.015 to 0.03 wt% carbon (C).

11. A container according to any one of claims 9 to 10, wherein the filler material is AISI 316LMn steel.

12. Use of a container according to any one of claims 9 to 11 for storing or transporting liquid ammonia.

13. A method for storing or transporting liquid ammonia, comprising the step of storing or transporting liquid ammonia in a container made of the austenitic stainless steel defined in any one of claims 1 to 8.

14. A method for storing or transporting two fuels, at least one of which is liquid ammonia, comprising the step of storing or transporting the two fuels simultaneously in two separate compartments of the same container, wherein the container is made of austenitic stainless steel as defined in any one of claims 1 to 8.